The Effect of Emollient Oils in Preterm Infants: A Systematic Review and Meta-Analysis - Rita Wahyuni; Happy Hayati; Mega Hasanul Huda (Indonesian Journal of Global Health Research, 2025)
Premature infants have distinct physiological differences in their skin compared to full-term infants, characterized by thinner skin and subcutaneous tissue due to an underdeveloped stratum corneum. Several non-pharmacological therapies are implemented to improve the skin integrity of premature infants. However, the effectiveness of these therapies needs to be explored further to establish their role in enhancing skin care and overall health outcomes in this vulnerable population. Objective to identify the effectiveness of non-pharmacological interventions on the skin condition and health outcomes of preterm infants, and to determine which intervention is most effective in improving skin condition and health outcomes. In this meta-analysis, randomized controlled trials (RCTs) of emollient oil administration interventions were systematically searched across four databases including Pubmed, Science Direct, Oxford Academic, and Cochrane. The studies that met the eligibility criteria were independently assessed for methodological quality, and data extraction was performed by two investigators. A total of 8 trials were identified, encompassing 3637 participants. To analyze the data, a random-effects model was employed, along with subgroup analysis and meta-regression analysis to explore the effects of different intervention components. Coconut oil and sunflower seed oil were evaluated for their effects on skin condition using the NSCS. The results indicated that sunflower seed oil was significantly more effective in reducing the NSCS score, with a p-value of 0.001 (95% CI = 1.426 to -0.364). Liquid Vaseline in the control group also showed significant results, with a p-value of 0.001 (95% CI = -1.426 to -0.364). In terms of weight gain and the incidence of hypothermia, there were no significant differences between the two oils and the control group. Administration of the oils once a day for a longer duration proved to be more effective in improving the infants' skin condition. Evidence suggests that the use of coconut oil and sunflower seed oil is effective in increasing body weight and reducing the incidence of hypothermia and sepsis. Furthermore, sunflower seed oil appears to be more effective than coconut oil in improving skin condition. Based on these findings, it is recommended that policymakers and healthcare professionals consider incorporating coconut oil or sunflower seed oil emollients into the routine care of premature infants.